Changes of Western honey bee Apis mellifera ligustica (Spinola, 1806) ventriculus microbial profile related to their in-hive tasks. Issue 1 (1st January 2021) - Cilia, Giovanni; Fratini, Filippo; Tafi, Elena; Mancini, Simone; Turchi, Barbara; Sagona, Simona; Cerri, Domenico; Felicioli, Antonio; Nanetti, Antonio
Abstract : The effects of in-hive tasks on the honey bee ( Apis mellifera L.) ventriculus microbial profile were investigated by analysing honey bees belonging to six in-hive tasks (newly-emerged, nurses, wax builder, guardians, young foragers, old foragers). Total viable aerobic bacterial count, Enterobacteriaceae, staphylococci, Escherichia coli, lactic acid bacteria, Pseudomonas spp., aerobic bacterial endospores, and Enterococcus spp. were determined using a culture-based method. Significant in-hive tasks-dependent microbial profiles were detected for all cultured bacteria ( p  < 0.001), with the lowest values for newly-emerged and wax builder and the highest for old foragers. Pseudomonas spp. and Staphylococcus spp. were quantitatively lower in young foragers than in old foragers, while they were absent in the other investigated in-hive tasks. E. coli and Enterococcus spp. were detected only in old foragers. 1Lactic acid bacteria were higher in nurses and old foragers compared to the other in-hive tasks, while the newly-emerged showed the lowest amount of lactic acid bacteria. The results from this investigation showed that ventriculus microbiological profile of Apis mellifera ligustica undergoes changes based on the in-hive task, and, as concerns foragers, on their age.